Aqueous Extract of Mori Folium Exerts Bone Protective Effect Through Regulation of Calcium and Redox Homeostasis via PTH/VDR/CaBP and AGEs/RAGE/Nox4/NF-κB Signaling in Diabetic Rats - Liu, Chenyue; Zhu, Ruyuan; Liu, Haixia; Li, Lin; Chen, Beibei; Jia, Qiangqiang; Wang, Lili; Ma, Rufeng; Tian, Simin; Wang, Min; Fu, Min; Niu, Jianzhao; et al. (Frontiers in Pharmacology, 2018)
Purpose: The present study is aimed to explore whether the aqueous extract of Mori Folium (MF) exhibits bone protective effect by regulating calcium and redox homeostasis in diabetic rats, and to identify the signaling pathways involved in this process. Methods: Diabetic rats were established using high-sugar and high-fat diet and streptozotocin . Histopathological alterations in the femurs were evaluated by the stainings of hematoxylin-eosin and alizarin red S. In addition, femoral strength was detected by a three-point bending assay, bone microstructure was detected with micro-computer tomography. Bone material properties were examined by Fourier-transform infrared spectroscopy. Furthermore, the expressions of IGF-1, runt-related transcription factor 2 (Runx2), osteoprotegerin (OPG), receptor activator of nuclear factor kappa-Β ligand (RANKL), cathepsin K, AGEs, receptor of advanced glycation end products (RAGE), NADPH oxidase 4 (Nox4), and nuclear factor kappa-B (NF-κB) in the femurs and tibias, and the alterations in the levels of calcium-binding protein-28k (CaBP-28k), transient receptor potential V6 (TRPV6), and vitamin D receptor (VDR) in the kidneys and duodenums were determined by western blot and immunohistochemical analysis. Results: MF treatment upregulates the expression of OPG, downregulates the expressions of AGEs, RAGE, Nox4, NF-κB and RANKL, which leads to improve bone microstructure and strength exhibited by an increase in cortical area ratio, cortical thickness and trabecular area ratio as well as ultimate load, elastic modulus, and bending stress in the femurs and tibias of diabetic rats. In addition, MF aqueous extract preserves bone material properties by decreasing the ratio of fatty acid/collagen and increasing the ratio of mineral/matrix in the femurs of diabetic rats. Moreover, MF treatment upregulates the expressions of TRPV6 and VDR in the duodenums and CaBP-28k in the kidneys of diabetic rats. Additionally, MF has ability of increasing the levels of SOD and TAC as well as decreasing the levels of IL-6, AGEs, MDA and 8-OH-dG. Conclusions: MF treatment may improve bone quality through maintenance of calcium homeostasis via regulating the PTH/VDR/CaBP signaling, and elimination of oxidative stress via regulating the AGEs/RAGE/Nox4/NF-κB signaling. These results may suggest the potential of MF in preventing the development of diabetic osteoporosis.